The Effect of Learning Discipline on Student Learning Achievement MA Tanada Waru Sidoarjo - Sirojuddin Abror; Cholifatul Azizah; Amalia Salsabilla (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This research writing is arranged with the desire to realize the goal of the influence produced by learning discipline on the learning achievement of students of MA TANADA Waru Sidoarjo. The use of methods or methods carried out in the study is quantitative survey type, the population that the researcher took was all students of MA TANADA Waru Sidoarjo as many as 36 as well as the sample taken which is the same as the population if less than 100 then the technique used is total sampling. The first observation was carried out by looking at the condition of the school and interviewing the curriculum vice principal, then making a questionnaire to be distributed to respondents, namely students, and no less important evidence of important documents or files as research material, this method is the data collection technique used in this study. The data collected after that is time to analyze using the provisions of quality testing, assumption testing, and simple regression with one variable of learning discipline. Based on the results of the t-test, the value that matches the significance is proven, meaning the hypothesis is accepted and has a significant effect between the variable of learning discipline on student learning achievement. Efforts that can be made by MA TANADA Waru Sidoarjo school are by using various new strategies or methods to foster students' enthusiasm in learning discipline such as rewards or punishments which in this case students consciously do so that they can encourage achievement in learning.